PSYCHOLINGUISTIC STUDY OF SWEARING AND FREEDOM OF SPEECH - Musdalifah Dachrud; Ardianto; Edi Gunawan; Arthur Gerung (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
We cannot denied that every language has Swear word in it. Language as communication and the accumulation of knowledge is a cognitive system, so it connected to many psychological aspects and to various areas of human brain. Swearing can be active in the left hemisphere, which regulates language as well as the right hemisphere because it provokes emotions.However, connection between brain and swearing is deeply embedded in human brain, we can see in in post-stroke aphasia patients and in corprolalia condition of people with Tourette’s syndrome who cannot control swearing due to damage to the limbic system and basal galia. Swearing in certain social situations can be positive and increase pain tolerance. Swearing has an important function in human biopsychosocial Behavior. Indeed, there are many negative things about swearing, but prohibiting them with the threat of criminal punishment is not the best solution.